Three-dimensional gait characteristics of patients after unilateral total knee arthroplasty. Issue 34 (27th August 2021) - Wang, Zong-Han; Wang, Jin-Cheng; Zheng, Shuang; Xue, Pan; Han, Fu-Jun
Abstract : Abstract: The purpose of this study is to evaluate the gait characteristics of bilateral limbs after unilateral total knee arthroplasty (TKA) using three-dimensional (3D) dynamic capture technology. Forty-two patients who underwent TKA were selected from the Orthopedic Medical Center of The Second Hospital of Jilin University from November 2018 to May 2019. We used a 3D dynamic capture system to measure the gait characteristics of patients at 3 months after TKA. The data, including relative position and direction of different body parts, the force between feet and ground, spatial and temporal relationship of the lower limb muscles, were measured. Besides, the surface electromyogram signal and the force plate analog signal were also collected. The walking ability, knee 3D kinematic, and kinetic characteristics were analyzed by the Cortex software. Spatial and temporal parameters, including stride frequency, double support phase, single support phase, step length, step time, step width, stride length, gait cycle, velocity, were no significant difference in bilateral lower extremities ( P  > .05). The reaction force of hip, knee, and ankle joint in the operation side were less than that of the healthy side, but the difference was not statistically significant ( P  > .05). However, when compared with the healthy side, the hip joint in operation side had a larger maximum extension angle ( P  < .001), the knee joint in operation side had a larger maximum valgus angle and valgus activity ( P  < .05), and had a smaller tibial maximum internal rotation angle ( P  < .05). Besides, the surface electromyogram signals of tibialis anterior muscles were reduced ( P  < .05). 3D gait analysis, as an objective and quantitative evaluation method, is a safe, effective, and reliable method for evaluating postoperative knee function. The data of gait analysis prove that TKA is a vital treatment to improve the function of patients with knee arthritis. Besides, gait analysis also showed that there were various kinematic and biomechanical abnormalities in the knee after TKA, which may be the reason why the surgical knee could not immediately return to normal level. Abstract : Supplemental Digital Content is available in the text